Tucatinib plus trastuzumab for chemotherapy-refractory, HER2-positive, RAS wild-type unresectable or metastatic colorectal cancer (MOUNTAINEER): a multicentre, open-label, phase 2 study. Issue 5 (May 2023) - Strickler, John H; Cercek, Andrea; Siena, Salvatore; André, Thierry; Ng, Kimmie; Van Cutsem, Eric; Wu, Christina; Paulson, Andrew S; Hubbard, Joleen M; Coveler, Andrew L; Fountzilas, Christos; Kardosh, Adel; et al.
Summary: Background: HER2 is an actionable target in metastatic colorectal cancer. We assessed the activity of tucatinib plus trastuzumab in patients with chemotherapy-refractory, HER2-positive, RAS wild-type unresectable or metastatic colorectal cancer. Methods: MOUNTAINEER is a global, open-label, phase 2 study that enrolled patients aged 18 years and older with chemotherapy-refractory, HER2-positive, RAS wild-type unresectable or metastatic colorectal cancer at 34 sites (clinics and hospitals) in five countries (Belgium, France, Italy, Spain, and the USA). Initially, the study was designed as a single-cohort study, which was expanded following an interim analysis to include more patients. Initially, patients were given tucatinib (300 mg orally twice daily) plus intravenous trastuzumab (8 mg/kg as an initial loading dose, then 6 mg/kg every 21 days; cohort A) for the duration of treatment (until progression), and after expansion, patients were randomly assigned (4:3), using an interactive web response system and stratified by primary tumour location, to either tucatinib plus trastuzumab (cohort B) or tucatinib monotherapy (cohort C). The primary endpoint was confirmed objective response rate per blinded independent central review (BICR) for cohorts A and B combined and was assessed in patients in the full analysis set (ie, patients with HER2-positive disease who received at least one dose of study treatment). Safety was assessed in all patients who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov, NCT03043313, and is ongoing. Findings: Between Aug 8, 2017, and Sept 22, 2021, 117 patients were enrolled (45 in cohort A, 41 in cohort B, and 31 in cohort C), of whom 114 patients had locally assessed HER2-positive disease and received treatment (45 in cohort A, 39 in cohort B, and 30 in cohort C; full analysis set), and 116 patients received at least one dose of study treatment (45 in cohort A, 41 in cohort B, and 30 in cohort C; safety population). In the full analysis set, median age was 56·0 years (IQR 47–64), 66 (58%) were male, 48 (42%) were female, 88 (77%) were White, and six (5%) were Black or African American. As of data cutoff (March 28, 2022), in 84 patients from cohorts A and B in the full analysis set, the confirmed objective response rate per BICR was 38·1% (95% CI 27·7–49·3; three patients had a complete response and 29 had a partial response). In cohorts A and B, the most common adverse event was diarrhoea (55 [64%] of 86), the most common grade 3 or worse adverse event was hypertension (six [7%] of 86), and three (3%) patients had tucatinib-related serious adverse events (acute kidney injury, colitis, and fatigue). In cohort C, the most common adverse event was diarrhoea (ten [33%] of 30), the most common grade 3 or worse adverse events were increased alanine aminotransferase and aspartate aminotransferase (both two [7%]), and one (3%) patient had a tucatinib-related serious adverse event (overdose). No deaths were attributed to adverse events. All deaths in treated patients were due to disease progression. Interpretation: Tucatinib plus trastuzumab had clinically meaningful anti-tumour activity and favourable tolerability. This treatment is the first US Food and Drug Administration-approved anti-HER2 regimen for metastatic colorectal cancer and is an important new treatment option for chemotherapy-refractory HER2-positive metastatic colorectal cancer. Funding: Seagen and Merck & Co.